Heart rate responses during sport-specific high-intensity circuit exercise in child female gymnasts - Salagas, A.; Donti, O.; Katsikas, C.; Bogdanis, G. C. (Sports, 2020)
This study examined heart rate (HR) responses during a sport-specific high-intensity circuit training session to indirectly assess cardiorespiratory stress in child athletes. Seventeen, female gymnasts, aged 9-11 years performed two 5-min 15 s sets of circuit exercise, interspersed by a 3 min rest interval. Each set included five rounds of five gymnastic exercises (7 s work, 7 s rest) executed with maximal effort. During the first circuit training set, peak heart rate (HR) was 192 ± 7 bpm and average HR was 83 ± 4% of maximum HR (HRmax), which was determined in a separate session. In the second set, peak HR and average HR were increased to 196 ± 8 bpm (p < 0.001, d = 0.55) and to 89 ± 4% HRmax (p < 0.001, d = 2.19), respectively, compared with the first set. HR was above 80% HRmax for 4.1 ± 1.2 min during set 1 and this was increased to 5.1 ± 0.4 min in set 2 (p < 0.001, d = 1.15). Likewise, HR was above 90% of HRmax for 2.0 ± 1.2 min in set 1 and was increased to 3.4 ± 1.7 min in set 2 (p < 0.001, d = 0.98). In summary, two 5-min 15 s sets of high-intensity circuit training using sport-specific exercises, increased HR to levels above 80% and 90% HRmax for extended time periods, and thus may be considered as an appropriate stimulus, in terms of intensity, for improving aerobic fitness in child female gymnasts.